Gender relations and women's reproductive health in South Sudan - Sumit Kane; Matilda Rial; Anthony Matere; Marjolein Dieleman; Jacqueline E.W. Broerse; Maryse Kok (Taylor & Francis Group, 2016)
Background: In South Sudan, women disproportionately bear the burden of morbidity and mortality related to sexual and reproductive health, with a maternal mortality ratio of 789 deaths per 100,000 live births. Design: A qualitative study was conducted to analyze how gendered social relations among the Fertit people affect women's ability to exercise control over their reproductive lives and thereby their sexual and reproductive health. Transcripts of 5 focus group discussions and 44 semi-structured interviews conducted with purposefully selected community members and health personnel were analyzed using Connell's relational theory of gender. Results: Women across all age groups report that they have little choice but to meet the childbearing demands of husbands and their families. Women, both young and old, and also elders, are frustrated about how men and society are letting them down and how they are left to bear the reproductive burden. The poverty and chronic insecurity in South Sudan mean that many men have few sources of pride and achievement; conformity and complicity with the hegemonic practices accord both security and a sense of belonging and privilege to men, often at the expense of women's reproductive health. Conclusions: Inequalities in the domestic, social, and economic spheres intersect to create social situations wherein Fertit women's agency in the reproductive realm is constrained. In South Sudan, as long as economic and social opportunities for women remain restricted, and as long as insecurity and uncertainty remain, many women will have little choice but to resort to having many children to safeguard their fragile present and future. Unless structural measures are taken to address these inequalities, there is a risk of both a widening of existing health inequalities and the emergence of new inequalities.